2016
DOI: 10.1007/s11010-016-2770-6
|View full text |Cite
|
Sign up to set email alerts
|

The increased level of COX-dependent arachidonic acid metabolism in blood platelets from secondary progressive multiple sclerosis patients

Abstract: Platelet activation is increasingly postulated as a possible component of the pathogenesis of multiple sclerosis (MS), especially due to the increased risk of cardiovascular events in MS. Arachidonic acid cascade metabolized by cyclooxygenase (COX) is a key pathway of platelet activation. The aim of our study was to investigate the COX-dependent arachidonic acid metabolic pathway in blood platelets from secondary progressive multiple sclerosis (SP MS) patients. The blood samples were obtained from 50 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 60 publications
(70 reference statements)
0
30
0
Order By: Relevance
“…After several years of the disease's duration, when the axons have lost their ability to regenerate, in more than 80% of cases RRMS turns into a secondary progressive stage (SPMS), in which the patient suffers irreversible progressive disability. [12][13][14] The available data, including our previous studies, clearly indicate excessive intravascular activation of these cells and their hyperresponsiveness to the number of physiological activators in SPMS. 3 The nature of the pathophysiology of MS is very complex and almost always involves multiple types of cells.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…After several years of the disease's duration, when the axons have lost their ability to regenerate, in more than 80% of cases RRMS turns into a secondary progressive stage (SPMS), in which the patient suffers irreversible progressive disability. [12][13][14] The available data, including our previous studies, clearly indicate excessive intravascular activation of these cells and their hyperresponsiveness to the number of physiological activators in SPMS. 3 The nature of the pathophysiology of MS is very complex and almost always involves multiple types of cells.…”
mentioning
confidence: 70%
“…That is, ischaemic events are directly associated with irregular platelet functions and their prothrombotic activity. [12][13][14] A study scheduled by our research group will, for the first time, direct the search for the origins of the hyperactivity of platelets towards molecular changes within platelets in SPMS. 17 Our existing findings state that platelet activation is an epiphenomenon consequent to the progression of MS, and probably secondary to endothelial injury, which causes the exposure of platelets to a variety of stimuli.…”
mentioning
confidence: 99%
“…The possible involvement of platelets in MS was first investigated by Putnam in 1937(Putnam 1937). In the 1950-1960s several studies (Nathanson andSavitsky 1952, Wright et al 1965) were focused on the relations of platelets to CNS demyelination and reported increased platelet adhesiveness correlated with activity of MS (Morel et al 2015(Morel et al , 2016) (such as fibrin, tissue factor, protein C) in lesion of MS patients suggests procoagulant state (Han et al 2008). Abnormalities of platelet reactivity in MS patients and chronic platelet activation in MS seem to be well established (Morel et al 2015(Morel et al , 2016.…”
Section: The Potential Role Of Blood Platelets In Multiple Sclerosismentioning
confidence: 99%
“…In the 1950-1960s several studies (Nathanson andSavitsky 1952, Wright et al 1965) were focused on the relations of platelets to CNS demyelination and reported increased platelet adhesiveness correlated with activity of MS (Morel et al 2015(Morel et al , 2016) (such as fibrin, tissue factor, protein C) in lesion of MS patients suggests procoagulant state (Han et al 2008). Abnormalities of platelet reactivity in MS patients and chronic platelet activation in MS seem to be well established (Morel et al 2015(Morel et al , 2016. Sheremata and others (2008) reported increased platelet activation assessed by the elevated levels of platelet activation markers such as platelet MPs and P-selectin on platelet membranes in MS patients.…”
Section: The Potential Role Of Blood Platelets In Multiple Sclerosismentioning
confidence: 99%
“…The combination of COX-2 and 5-LOX selective inhibitors has the potential to improve multiple sclerosis pathology. Moreover, multiple sclerosis has been associated with platelet activation and augmented cardiovascular risk, which are considered as causal factors in the pathogenesis of the disease (57,58). Interestingly, it has been recently observed that peripheral blood platelets of patients highly express COX-2 (58).…”
Section: Nsaids Administration: Future Perspectivesmentioning
confidence: 99%